2019
DOI: 10.1115/1.4043246
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Investigation on the Feasibility of Horizontal Drilling With a New Type of Jet Mill Bit

Abstract: Recently, a new type of jet mill bit (JMB) has been introduced to improve the cutting transport efficiency in horizontal drilling by comminuting cuttings into dust-like particles immediately after the cuttings are generated. To promote the application of JMBs in the field, in this work, JMBs were further improved by including junk slots (JS) all around to allow cuttings to flow through the annulus and thereby prevent sticking from occurring while tripping out. Moreover, numerical and experimental investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Since drilling fluids flowing in a borehole follows conservation laws, including mass conservation, energy conservation, and momentum conservation, it can be regarded as a continuous, incompressible turbulent flow of a single medium [31,32]. Then, the governing equations could be derived.…”
Section: Governing Equations and Boundary Conditions For Cfd Simulationmentioning
confidence: 99%
“…Since drilling fluids flowing in a borehole follows conservation laws, including mass conservation, energy conservation, and momentum conservation, it can be regarded as a continuous, incompressible turbulent flow of a single medium [31,32]. Then, the governing equations could be derived.…”
Section: Governing Equations and Boundary Conditions For Cfd Simulationmentioning
confidence: 99%
“…Please note that the junk slots or flowby of the depressure-dominated JMB is much smaller than that of the conventional bits and so is the clearance in the annulus. As Cao et al (2019) reported, the cuttings will flow out inside the bit through the cuttings-suction channel instead of the small junk slots and annulus. The other stream flows through the backward jet nozzles, mixing chamber, throat, dissociating and comminution tube, and diffuser toward the annulus between open hole and drill pipe.…”
Section: Introductionmentioning
confidence: 95%
“…Through depressuring at the bottom hole, the JMB can lower the stress on rock surface, minimize cuttings hold-down effect, and improve cuttings cleaning capacity, thus increasing the ROP (Li et al 2010;Shi et al 2018). In 2019, JMB was improved by adding junk slots around to allow cuttings to flow through the annulus instead of accumulating at the top of the JMB while tripping out and therefore avoid sticking (Cao et al 2019). This improvement reduces the risk of sticking while tripping out and increases the feasibility of field application of JMB in horizontal drilling.…”
Section: Introductionmentioning
confidence: 99%